Penyuluhan dan Pelatihan Stimulasi Periode Emas Anak 1000 HPK di Wilayah Puskesmas Sipoholon, Kabupaten Tapanuli Utara Tahun 2019 - Sulastry Pakpahan (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
National data according to the Indonesian Ministry of Health in 2015, 11.5% of children under five in growth and development of abnormalities. Knowledge and awareness of the importance of stimulation of growth and development during the 1000 HPK period is needed so that parents can take advantage of this period to form children who have intellectual, emotional, language, creative and positive character. Activities carried out by providing counseling to pregnant women, mothers or husbands with toddlers and training to health cadres. The implementation of the activity lasts 3 days, divided into 2 stages, namely day 1-2 is the implementation of health education and day 3 is the implementation of training. The number of health education participants was 57 people and training participants were 48 people. Each participant was given a questionnaire to measure the increase in knowledge after the implementation of the activity. The results of this activity was obtained that the participants' knowledge increased by 24.56% in very good categories, 22.8% in good categories, and 43.38% in adequate categories. The increase in the knowledge of the training participants in the very good category increased by 27.1%, the good category was 20.8% and the moderate category was 47.9%. Health education and training about growth and development stimulation during the 1000 HPK period can increase knowledge and awareness of mothers, families and health cadres so they are expected to be able to apply the knowledge received during the training in everyday life and to the surrounding community.